2013
DOI: 10.1136/bmjopen-2013-003701
|View full text |Cite
|
Sign up to set email alerts
|

Drugs causing adverse events in patients aged 45 or older: a randomised survey of Australian general practice patients

Abstract: ObjectiveTo determine prevalence of adverse drug events (ADEs) in patients aged 45 years or older presenting to Australian general practitioners (GPs) and identify drug groups related to ADEs, their severity and manifestation.DesignSubstudy of the Bettering the Evaluation and Care of Health continuous survey of Australian GP clinical activity in which randomly selected GPs collected survey data from patients. Data are reported with 95% CIs.SettingGeneral practice in Australia.Main outcome measuresPrevalence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 21 publications
(18 reference statements)
1
25
0
Order By: Relevance
“…Miller et al [40] reported 11.6% of people had at least one AE in the preceding six months, most of which were mild to moderate; 11.8 were severe and 5.4% required a hospital admission as a result of using 13 commonly prescribed medicines not on lists such as BEERS Criteria [15,16]. These tools were developed to aid medicine prescribing decisions, not replace reasoned clinical decision-making.…”
Section: Strategies That Can To Improve Medicine Safety and Reduce Mementioning
confidence: 99%
“…Miller et al [40] reported 11.6% of people had at least one AE in the preceding six months, most of which were mild to moderate; 11.8 were severe and 5.4% required a hospital admission as a result of using 13 commonly prescribed medicines not on lists such as BEERS Criteria [15,16]. These tools were developed to aid medicine prescribing decisions, not replace reasoned clinical decision-making.…”
Section: Strategies That Can To Improve Medicine Safety and Reduce Mementioning
confidence: 99%
“…• about a quarter of patients at encounters and 16.2% of people in the population had six or more diagnosed chronic conditions 65 106 Of the 11,181 patients aged 65+ in our sample, the average number of diagnosed chronic conditions among them was 4.2 (median = 4) and ranged from 0 to 21. Prevalence and management of chronic conditions Table 14.1 shows the prevalence and management rates of common chronic conditions among patients aged 65+.…”
Section: Number Of Chronic Conditions In People Aged 65+mentioning
confidence: 99%
“…Readers interested in adverse drug events will find more detailed information from the BEACH program in Drugs causing adverse events in patients aged 45 or older: a randomised survey of general practice patients. 65 …”
Section: Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…76 Readers interested in adverse drug events will find more detailed information from the BEACH program in Drugs causing adverse events in patients aged 45 or older: a randomised survey of general practice patients. 77 …”
Section: Medicationsmentioning
confidence: 99%